Fantasia in “Al Reesh Novel” by Saleem Barakat - اىٍػرس الدکخٔر ركاد نٍال ٌهٍفٕ (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The current research is trying to study one of the novelistic works of the Kurdish author Saleem Barakat which is (Al Reesh novel), through analyzing the fantasia which is the dominant figure in the novel so as to uncover the intellectual purpose of this figure , in addition to its valuable beauty,through the Interpretation Style. The importance of this research can be noticed through studying the work of a celebrated novelist,who has proved his mastery in literature through his unfamiliar style, superb works and turbulent irritable language . The research plan is consisted of a preface about the narrative fantasia, and three sections. First section is dealing with the fantasia of actions, the second section deals with the fantasia of characters, and the third section is about dialogues, attached with a conclusion of the most outcomes of the research ..